THE INFLUENCE OF KNOWLEDGE, RELIGIOSITY, AND POCKET MONEY ON STUDENTS' INTEREST FOR SAVING IN SHARIA COMMERCIAL BANKS - Fanny Qurrati A’inina; Mardi Mardi; Santi Susanti (Transpublika Publisher, 2021)
This research aims to determine the effect of Knowledge, Religiosity, and Pocket Money on interest for saving in shariah banks. Data collection techniques using questionnaires and using primary data with a population of 503 students from the Faculty of Economics at the State University of Jakarta. The sample selection was done by proportional random sampling technique which resulted 205 samples. Data analysis uses several regression analyses with the help of SPSS. The results showed: (1) Partial knowledge has a positive and significant effect on interest in saving. (2) Partial religiosity does not affect interest in saving. (3) Partial pocket money has a positive and significant effect on interest in saving. (4) Knowledge, religiosity and pocket money simultaneously affect interest in saving.